Student’s English (Islamic) Vocabulary Of STIT Muhammadiyah Tempurejo Ngawi - Nining Wulandari (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
Nowadays, the mastery of the vocabulary in mastering English is an absolute necessity. A person can never speak English if they do not have good vocabulary mastery. Vocabulary has a very important role in shaping language skills for someone. Teaching by emphasizing aspects of English language skills including Islamic vocabulary aspects may need to be considered to applied in the future. If this idea can be realized by them vocabulary teaching as an important component in teaching English will receive its own attention. The purpose of this study was to get a picture of the mastery of English vocabulary of students majoring in Islamic Religious Education (PAI) STIT Muh Tempurejo Ngawi. The researcher put forward in this study is the mastery of English Islamic vocabulary of students majoring in Islamic Religious Education (PAI) STIT Muh Tempurejo Ngawi in general is quite good. This research uses descriptive methods with data collection techniques and data analysis techniques through questioner and ability test (competence test). Data obtained through ability tests were analyzed using the mean formula and standard deviation (Nasrum Harahap in Gunardi 1988: 33). The population of this study were students of Islamic Religious Education (PAI) STIT Muh Tempurejo Ngawi academic year 2018-2019, using random sampling, namely one class as a respondent, who worked on the test questions given at once answer / fill in the distributed questionnaire. Based on the results of research and discussion, it was concluded that the mastery of English vocabulary of students of Islamic Religious Education (PAI) STIT Muh Tempurejo Ngawi is good. The results obtained showed that the majority of students (respondents) scored in both good and very good categories. Keyword : English learning, Islamic vocabulary.